Strategi Penerapan Deep Learning di SMK Swasta: Deep Learning Implementation Strategy in Private Vocational Schools - Sumardi, Kamin; Setiawan, Agus; Rohendi, Dedi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Deep learning is a policy currently being implemented in primary and secondary education, as well as in vocational schools. The implementation of deep learning in learning in vocational schools requires an exceptional understanding for teachers. This training aims to gather data and facts about the knowledge, experience, and implementation of deep learning among private vocational school teachers. The method employed is in-house training, utilizing a participatory and collaborative approach. The training was held at LPS Ciamis Private Vocational School. The training participants were 40 private vocational school teachers. The instrument used was a questionnaire using Google Forms. The results of the training showed that an average of 68% of private vocational school teachers already had a deep understanding of learning. As many as 15.8% of private vocational school teachers are familiar with the basic concept of deep learning. This knowledge was obtained from social media, friends, and the web, to the extent of 31.6%, 26.3%, respectively. As many as 89.5% of private vocational school teachers agreed that deep learning can improve the quality of learning. The teachers already have a high degree of understanding of the purpose of implementing deep learning in vocational schools, with approximately 98% understanding. 47.4% of private vocational school teachers are ready to implement deep learning, while 47.4% of private vocational school teachers are not ready to implement deep learning. Thus, deep learning still requires intensive socialization and training so that vocational school teachers can implement deep learning into the subjects they teach.